Sam's letters to Jennifer - Patterson, James (London : Headline Book Publishing, 2004)
Grief-stricken by a recent tragedy, Jennifer returns to the resort village where she grew up to help her beloved grandmother. There, Jennifer will discover new meaning in life and experience not one, but two of the most amazing love stories ever.
Keywords: Letters -- Fiction; Love stories